Potential antifungal impact of citral and linalool administered individually or combined with fluconazole against clinical isolates of Candida krusei - Mehdi Houshmandzad; Aghil Sharifzadeh; Alireza Khosravi; Hojjatollah Shokri (Shahrekord University of Medical Sciences, 2022)
Introduction: Candida krusei is recognized as a major fungal pathogen in patients with immunodeficiency disorders. The present study aimed at investigating the anticandidal activities of citral and linalool combined with fluconazole (FLZ) against FLZ-resistant C. krusei strains. Methods: Antifungal activities were evaluated by the broth microdilution (MD) method to determine the minimum inhibitory and fungicidal concentrations (namely, MICs and MFCs) according to the Clinical and Laboratory Standards Institute (CLSI) M27-A3 document. The interactions were further evaluated using fractional inhibitory concentration indices (FICIs) for combinations of citral+FLZ and linalool+FLZ, calculated from checkerboard MD assays. Results: The mean ± standard deviation (SD) MIC values of citral, linalool, and FLZ against the C. krusei isolates were 70.23 ± 17, 150 ± 38.73, and 74.66 ± 36.95 μg/mL, respectively. Some fungicidal activities were also observed for citral (2.5) and linalool (1.53) against the C. krusei isolates. The FICI values of citral+FLZ and linalool+FLZ for the C. krusei isolates ranged from 0.4 to 1.00 and 0.19 to 0.63, respectively. The additive and synergistic interactions of linalool + FLZ were further observed in 12 (57.1%) and 9 (42.9%) C. krusei isolates. However, there was an additive interaction for citral + FLZ in 17 (80.9%) isolates. They also showed a synergistic interaction in only four (19.1%) isolates. Moreover, linalool and citral plus FLZ did not have any antagonistic effect on any isolates. Conclusion: The study findings support the possible capabilities of citral and linalool, as anticandidal agents, and FLZ might be supplemented with citral and/or linalool for treating FLZ-resistant C. krusei infections.